Geological framework and morphotectonic characterization of the Khon Kaen Geopark, Northeastern Thailand - Vimoltip Singtuen; Porawat Joosakoon; Burapha Phajuy; Punya Charusiri (Scientific Reports)
Abstract Khon Kaen Geopark (KKGp), located in the Western margin of the Khorat Plateau (Northeastern Thailand), showcases a complex topographic and structural framework shaped by regional tectonics. The area is underlain by the Mesozoic Khorat Group, comprising the Nam Phong, Phu Kradung, Phra Wihan, Sao Khua, Phu Phan, Khok Kruat, and Maha Sarakham Formations. This study integrates field-based structural analysis, satellite imagery, and seismic interpretation to investigate the tectonic evolution and geomorphological development of KKGp. The Western sector features a multiphase syncline forming mountainous terrain surrounding a central basin, with a strike-slip fault system to the South. In contrast, the eastern sector is defined by an anticline flanked by a central thrust fault and a reverse fault along its eastern margin, producing a relatively subdued landscape. Structural trends—N–S, NW–SE, and NE–SW—reflect multiple tectonic events. The interplay between tectonics and lithological variation has critically influenced modern geomorphology.